Peran Mahkamah Konstitusi Dalam Perlindungan Hak Asasi Manusia: Tinjauan Hukum Tata Negara - Reynold Simanjuntak; Rahmawaty Arsyad (CV. ITTC INDONESIA, 2024)
The Constitutional Court (MK) functions as the final interpreter of the constitution and guardian of human rights (HAM) in Indonesia. The Constitutional Court's duties include reviewing the constitutionality of laws, ensuring that regulations are in line with the 1945 Constitution, and safeguarding individual rights through decisions that strengthen the basic rights of every citizen. Apart from that, the Constitutional Court also helps resolve election disputes to maintain the integrity of the democratic system. The Constitutional Court's crucial decisions, such as regarding freedom of expression, protection of the rights of minority groups, and the right to legal protection in detention, reflect this institution's dedication to upholding human rights. However, challenges in implementing MK decisions include the public's low understanding of law, complex bureaucratic procedures, and resistance from parties with certain interests. Success in upholding human rights depends on political commitment, support from relevant institutions, and community acceptance of the necessary changes.